I need this problem solved.

## solve 5(2z-3) = 9(z-3)

Tutors, please sign in to answer this question.

# 1 Answer

Think Order of Operations, PEMDAS, parentheses, exponents, multiply and divide, add and subtract.

First you have to distribute the 5 on the left side and the 9 on the left side to each term in the corresponding parentheses.

5(2z-3)=9(z-3)

5*2z-5*3 = 9*z-9*3

10z-15 = 9z-27

then add 15 to both sides

10z=9z-12

then subtract 9z from both sides

z=-12

that's your answer! Just go through the order of operations and remember whatever you do to one side of the equation you must do to the other.